The Cognitive Cost of Anticholinergic Burden: Decreased Response to Cognitive Training in Schizophrenia - Vinogradov, Sophia; Fisher, Melissa; Warm, Heather; Holland, Christine; Kirshner, Margaret A.; Pollock, Bruce G. (The American journal of psychiatry, 2009)
Objective: Schizophrenia is treated with medications that raise serum anticholinergic activity and are known to adversely affect cognition. The authors examined the relationship between serum anticholinergic activity and baseline cognitive performance and response to computerized cognitive training in outpatients with schizophrenia. Method: Fifty-five patients were randomly assigned to either computerized cognitive training or a computer games control condition. A neurocognitive battery based on the Measurement and Treatment Research to Improve Cognition in Schizophrenia (MATRICS) initiative was performed at baseline and after the intervention. Serum anticholinergic activity, measured at study entry by radioreceptor assay, was available for 49 patients. Results: Serum anticholinergic activity showed a significant negative correlation with baseline performance in verbal working memory and verbal learning and memory, accounting for 7% of the variance in these measures, independent of age, IQ, or symptom severity. Patients in the cognitive training condition (N=25) showed a significant gain in global cognition compared to those in the control condition, but this improvement was negatively correlated with anticholinergic burden. Serum anticholinergic activity uniquely accounted for 20% of the variance in global cognition change, independent of age, IQ, or symptom severity. Conclusions: Serum anticholinergic activity in schizophrenia patients shows a significant association with impaired performance in MATRICS-based measures of verbal working memory and verbal learning and memory and is significantly associated with a lowered response to an intensive course of computerized cognitive training. These findings underscore the cognitive cost of medications that carry a high anticholinergic burden. The findings also have implications for the design and evaluation of cognitive treatments for schizophrenia.